Determining the effects of LFHV-PEF treatment on the water distribution and vigor of aged rice seeds using LF-NMR - Cheng, Ensi; Song, Ping; Hou, Tiangang; Zhang, Benhua; Wu, Liyan (International Journal of Agricultural and Biological Engineering, 2022)
This study aimed to investigate the effect of low-frequency high-voltage pulsed electric field (LFHV-PEF) treatment on the germination of aged rice seeds. Aged rice seeds were subjected to LFHV-PEF treatment with different electric field strengths, and low-field nuclear magnetic resonance (LF-NMR) was performed to acquire the LF-NMR data of rice seeds at different germination periods during a standard seed germination test to analyze their internal patterns of water state and distribution. Optimal treatment conditions were determined based on the physicochemical data collected during germination, and the improvements in seed vigor were verified. The findings indicated that during germination, the contents of bound and semi-bound water within the aged rice seeds initially increased and then decreased, whereas free water and total water contents increased continuously and rapidly. Side peaks were also observed within the seeds. Under the LFHV-PEF treatment, the semi-bound water within the seeds was more easily converted to free water, and the water absorption rate, germination potential, germination rate, germination index, and vigor index of these seeds improved. Further, the optimal electrical field strength was 12 kV. By analyzing the internal patterns of water state and distribution in seeds, the mechanism by which electric field treatment improved seed vigor was elucidated, thus, providing theoretical support and data evidence for research on water absorption during the germination of rice seeds, and methods for improving seed vigor. Keywords: aged rice seeds, germination, water phase, seed vigor, LF-NMR, LFHV-PEF DOI: 10.25165/j.ijabe.20221504.7590 Citation: Cheng E S, Song P, Hou T G, Wu L Y, Zhang B H. Determining the effects of LFHV-PEF treatment on the water and vigor of aged rice seeds using LF-NMR. Int J Agric & Biol Eng, 2022; 15(4): 190–196.